Risk of thyroid neoplasms in patients with 22q11.2 deletion and DiGeorge-like syndromes: an insight for follow-up - Walter Maria Sarli; Walter Maria Sarli; Silvia Ricci; Silvia Ricci; Lorenzo Lodi; Lorenzo Lodi; Federica Cavone; Lucia Pacillo; Lucia Pacillo; Lucia Pacillo; Carmela Giancotta; Graziamaria Ubertini; et al. (Frontiers in Endocrinology, 2023)
IntroductionThe chromosome 22q11.2 deletion syndrome comprises phenotypically similar diseases characterized by abnormal development of the third and fourth branchial arches, resulting in variable combinations of congenital heart defects, dysmorphisms, hypocalcemia, palatal dysfunction, developmental or neuropsychiatric disorders, and impairment of the immune system due to thymic dysfunction. Other genetic syndromes, often called DiGeorge-like, share clinical and immunological features with 22q11.2 deletion syndrome. This syndrome has been rarely associated with malignancies, mainly hematological but also hepatic, renal, and cerebral. Rarely, malignancies in the head and neck region have been described, although no aggregate of data on the development of thyroid neoplasms in patients with this clinical phenotype has been conducted so far.Materials and methodsTo characterize this possible association, a multicenter survey was made. Thus, we present a case series of five pediatric patients with 22q11.2 deletion syndrome or DiGeorge-like syndrome who were occasionally found with confirmed or highly suspected neoplasms of the thyroid gland during their follow-up. In three cases, malignancies were histologically confirmed, but their outcome was good due to an early recognition of suspicious nodules and precocious surgery.ConclusionsThis study underlines for clinicians the higher risk of neoplasms in the head and neck district for patients affected by these syndromes. It also emphasizes the importance of a prolonged clinical and ultrasound follow-up for patients with this clinical and immunological phenotype.